Prevalence of nonfermentative gram-negative bacilli and their antimicrobial susceptibility profiles in a tertiary care hospital of Eastern India - Sarkar, Mandira; Jena, Jagadananda; Pattnaik, Dipti; Mallick, Bandana (International Journal of Advances in Medicine, 2018)
Background: Nonfermentative gram-negative bacilli (nonfermenters) have emerged as a major concern for nosocomial infections. They exhibit resistance not only to the beta-lactam and other group of antibiotics but also to carbapenems. This study was undertaken to know the prevalence of nonfermenters from clinical samples along with their antimicrobial susceptibility profile. Methods: A cross-sectional study over a period of 21 months in the microbiology laboratory of a tertiary care hospital was done. Clinical samples were processed by conventional bacteriological methods for isolation and identification. Susceptibility testing was done by Kirby-Bauer disc diffusion method as recommended by Clinical and Laboratory Standard Institute. Results: 411 nonfermenters (13.18%) were isolated from 3116 culture positive clinical samples. Out of these nonfermenters, most were Acinetobacter baumannii (51.34%) followed by Pseudomonas aeruginosa (42.09%), Burkholderia cepacia complex (4.38%) and others (2.19%). Others included Burkholderia pseudomellei, Acinetobacter lwoffii and Stenotrophomonas maltophilia. Highest sensitivity to gentamicin and amikacin were shown by A. baumannii and P. aeruginosa respectively while both were mostly resistant to ceftriaxone. Burkholderia and Stenotrophomonas species showed 100% sensitivity to cotrimoxazole. A. baumannii was the most prevalent nonfermenter in intensive care units. Conclusions: Timely identification of nonfermenters and monitoring their susceptibility patterns will help in proper management of infections caused by them. Improved antibiotic stewardship and infection control measures should be implemented to prevent nosocomial infections and spread of drug resistant nonfermenters.